If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8g-5=-5(3g-3)
We move all terms to the left:
-8g-5-(-5(3g-3))=0
We calculate terms in parentheses: -(-5(3g-3)), so:We get rid of parentheses
-5(3g-3)
We multiply parentheses
-15g+15
Back to the equation:
-(-15g+15)
-8g+15g-15-5=0
We add all the numbers together, and all the variables
7g-20=0
We move all terms containing g to the left, all other terms to the right
7g=20
g=20/7
g=2+6/7
| -10.8=-1.2+v/6 | | 4-9v=-23 | | 7x+17-4x=5x-5 | | -8.8=3(3x-1)-9.8x | | 39=124x | | -8(h+11)=40 | | -3(e-5)=21 | | -7(6-h)=14 | | 2m-4=+3m-6 | | -11(5+w)=121 | | (x^2-x-6)/(2x^2+x-6)=0 | | 4^(3x-5)=26 | | 2x+6+3x-26=90 | | -9x-45=54 | | u-39=9 | | 5e=1 | | 26y+2(60-7y)=180 | | (x+50)(x+20)=400 | | 1=4/1c | | -3/7v-1/2=-3/5 | | 3(w-3)=w+5-4(-3w-1) | | 8x-10=3x+3=180 | | 2x-8+2(6x+5)=-2(x+8) | | -2(7x-8)+x=3(x+8) | | 4(u-4)-6=-5(-3u+2)-3u | | 5x10+50=180 | | 9*9*h=1620 | | 3y+y-2=22 | | 3y-y-2=22 | | 1-6x^2=-209 | | 22*2+6=y | | 8x=680/107 |